PENGARUH BUDAYA ORGANISASI TERHADAP PRODUKTIVITAS KERJA GURU HOMESCHOOLING HAYAT SCHOOL - Ariatpi, Fina; Wahyu Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of organizational culture on teacher work productivity at Homeschooling Hayat School. The background of this research is driven by the phenomenon of low teacher work productivity which is influenced by various factors, one of which is an unoptimal organizational culture. This study used a quantitative approach with a survey method, in which data were collected through questionnaires, observation, and documentation. The population in this study were all teachers who worked at Homeschooling Hayat School, with the sampling technique using total sampling. The data analysis technique used is simple linear regression analysis to test the hypothesis that has been proposed. The results showed that organizational culture has a significant influence on teacher work productivity at Homeschooling Hayat School. These findings are expected to contribute to the development of strategies to increase teacher work productivity through strengthening organizational culture in the educational environment.